Immunomodulatory Polysaccharide from Chlorophytum borivilianum Roots. (9th January 2011) - Thakur, Mayank; Connellan, Paul; Deseo, Myrna A.; Morris, Carol; Dixit, Vinod K.
Abstract : Chlorophytum borivilianum Santapau & Fernandes (Liliaceae) is an ayurvedic Rasayana herb with immunostimulating properties. The polysaccharide fraction (CBP) derived from hot water extraction of C. borivilianum (CB), comprising of ∼31% inulin-type fructans and ∼25% acetylated mannans (of hot water-soluble extract), was evaluated for its effect on natural killer (NK) cell activity ( in vitro ). Human peripheral blood mononuclear cells (PBMCs), isolated from whole blood on a Ficoll-Hypaque density gradient, were tested in the presence or absence of varying concentrations of each C. borivilianum fraction for modulation of NK cell cytotoxic activity toward K562 cells. Preliminary cytotoxicity evaluation against P388 cells was performed to establish non-cytotoxic concentrations of the different fractions . Testing showed the observed significant stimulation of NK cell activity to be due to the CBP of C. borivilianum . Furthermore, in vivo evaluation carried out on Wistar strain albino rats for humoral response to sheep red blood cells (SRBCs) and immunoglobulin-level determination using enzyme-linked immunosorbent assay (ELISA), exhibited an effectiveness of C. borivilianum aqueous extract in improving immune function. Present results provide useful information for understanding the role of CBP in modulating immune function.